Physical activity and sleep quality in military police officers Atividade física e qualidade de sono em policiais militares - Bernardo V.M.* (2018)
© 2018 Colégio Brasileiro de Ciências do EsporteThe study aimed to verify associations between physical activity level, sleep quality, excessive daytime sleepiness, and demographic characteristics of military police officers from Florianópolis and neighboring cities. An amount of 438 police officers had participated in the study. The instruments adopted were IPAQ, Pittsburgh Sleep Quality Index–PSQI; Epworth Sleepiness Scale–ESS; and a report with sociodemographic and occupational information. Military police officers were characterized by high levels of physical activity and poor sleep quality. Associations between physical activity level and sleep quality were not identified. Police officers that operate predominantly in administrative areas are considered less physically active than those operating in operational services.